2015
DOI: 10.1371/journal.pone.0134854
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postnatal Myostatin Inhibition on Bite Mechanics in Mice

Abstract: As a negative regulator of muscle size, myostatin (Mstn) impacts the force-production capabilities of skeletal muscles. In the masticatory system, measures of temporalis-stimulated bite forces in constitutive myostatin KOs suggest an absolute, but not relative, increase in jaw-muscle force. Here, we assess the phenotypic and physiologic impact of postnatal myostatin inhibition on bite mechanics using an inducible conditional KO mouse in which myostatin is inhibited with doxycycline (DOX). Given the increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…While both GH and IGF-1 are associated with increased muscle performance ( Gläser et al, 2010 ; Taekema et al, 2011 ), the effect of Mstn on muscle strength remains unclear. We have reported ( Williams et al, 2015 ) that MSTN inhibition may enhance overall strength due to hypertrophy, but that specific muscular force is not significantly different when normalized to muscle wet weights. Other studies have found that muscle fiber function is significantly reduced in MSTN -/- mice relative to muscle weights ( Amthor et al, 2007 ; Gentry et al, 2011 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While both GH and IGF-1 are associated with increased muscle performance ( Gläser et al, 2010 ; Taekema et al, 2011 ), the effect of Mstn on muscle strength remains unclear. We have reported ( Williams et al, 2015 ) that MSTN inhibition may enhance overall strength due to hypertrophy, but that specific muscular force is not significantly different when normalized to muscle wet weights. Other studies have found that muscle fiber function is significantly reduced in MSTN -/- mice relative to muscle weights ( Amthor et al, 2007 ; Gentry et al, 2011 ).…”
Section: Introductionmentioning
confidence: 91%
“…Muscle wasting is linked to excess Mstn in circulation ( Gonzalez-Cadavid et al, 1998 ; Marcell et al, 2001 ; Costelli et al, 2008 ). Mice overexpressing Mstn have less skeletal muscle than littermate controls ( Thomas et al, 2000 ; Lee, 2004 ; Huang et al, 2011 ), while MSTN gene mutations and reduced protein levels increase muscle mass ( Kambadur et al, 1997 ; Lin et al, 2002 ; Schuelke et al, 2004 ; Mosher et al, 2007 ; Williams et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our -/-mouse model the spatial-packing problem of enlarged musculature is conflated with reduced brain size, possibly due to suppressed myostatin expression within the brain (see Discussion), and with the structural effects of increased muscle and bite force (e.g. Byron et al, 2006;Williams et al, 2015). We therefore inferred the extricated and combined effects of brain and muscle growth on skull architecture in-silico and in doing so we also evaluate the ability of simple deformation to describe spatial-packing related phenomena.…”
mentioning
confidence: 88%
“…The mice were also used to indicate that a consistent amount of force needs to be applied over a much greater area of the craniofacial skeleton in the myostatin knockout, and this should, in turn, lead to altered biomechanical stress and bony morphology [3,16]. An MSTN −/− mouse has significantly larger temporalis, masseter, and medial and lateral pterygoid muscles than WT controls [17]. These characteristics, coupled with morphologic findings of the skull in MSTN −/− mice (e.g., shorter crania, longer, and rounder mandibles), provide further evidence of an altered craniofacial loading environment due to MSTN deficiency [3,16–20].…”
Section: Introductionmentioning
confidence: 99%